Customary Land Rights Of Orang Asli: A Case Study In Kampung Parit Gong, Negeri Sembilan, Malaysia - Kamilah Wati Mohd; Intan Nadia Ghulam Khan; Izawati Wook; Fareed Mohd Hassan (Universiti Sains Islam Malaysia, 2024)
Indexed by Scopus/MyCite